The chromosome-level genome of Hemerocallis middendorffii provides new insights into the floral scents and color biosynthesis in Chinese native daylily - Meiyu Sun; Baocai Han; Jianhua Xiao; Haiyan Yu; Yinli Jia; Shuhai Yuan; Juan Yao; Quan Xing; Dongqi Wu; Guofeng Sun; Jinzheng Zhang (BMC Plant Biology)
Abstract Background  Hemerocallis middendorffii is a kind of high quality ornamental plant with strong cold resistance, pleasant aroma, and gorgeous floral color. Hemerocallis is one of the three internationally recognized perennial flowers that has huge demand in the flower market. However, little is known about the floral scent and color biosynthesis in daylily due to the large genome size. Results We reported here a high-quality chromosome-scale genome of H. middendorffii which was a native daylily in China. Using PacBio HiFi and Hi-C sequencing technologies, we assembled a chromosome-level genome of 4.10 Gb with a contig N50 of 12.81 Mb. We identified 65,536 protein-coding genes across the 11 chromosomes. We employed a combination of genomic, transcriptomic, and metabolomic approaches to investigate mechanisms behind the floral scent and color biosynthesis in daylily. The main terpenoids contributing to floral fragrance were linalool, 3-carene, nerolidol, and α-farnesene, while carotenoids and anthocyanidins were the main components of floral color. These traits could be stably inherited by their hybrid progenies, and some of them exhibited heterosis. Through Weighted Gene Co-expression Network Analysis (WGCNA) analysis, we identified two modules MEblueviolet and MEgreenyellow related to terpenoids (floral scents) and carotenoids (floral colors) biosynthesis. The 10 hub genes including DXS, MVD, MVK, DXR, LCYBs, Z-ISO, CYPs, and JAS were screened by network construction. The results of qRT-PCR analysis showed that these hub genes were significant differentially expressed in daylily samples, and these results were basically consistent with the relative transcript levels of RNA-seq. Conclusions This study not only provides new insights into the molecular mechanisms of floral scent and color, but also lays a foundation for subsequent research on key gene functions and molecular breeding in Hemerocallis.